Mechanical Properties Improvement of Peat Soils Stabilized by Palm Oil Fuel Ash (POFA) based Geopolymer - Nurza Purwa Abiyoga; Dila Oktarise Dwina; Oki Alfernando; Fiona Dehansa Putri (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
Peat soils are generally characterized by high water content, significant organic matter composition, and relatively low shear strength compared to mineral soils. These properties may lead to excessive settlement and reduced load-bearing capacity, which can affect the performance of foundations and embankments constructed on peat deposits. Extensive peatland areas can be found in Jambi, Indonesia and innovative stabilization methods are required to enhance their mechanical properties for sustainable land use. This study develops an alternative method of stabilization by using palm oil fuel ash (POFA) as a base material for geopolymerization. POFA, an industrial by-product, is abundant in Jambi and offers a sustainable alternative to highly polluting Portland cement. The research methodology involved the preparation of geopolymer-stabilized peat samples with 0%, 10%, 15%, and 20% to total dry weight of POFA addition, followed by Unconfined Compressive Strength (UCS) tests to assess the improvement in soil strength. The results indicate a positive trend with increasing compressive strength values as the geopolymer content increases to 15%. The average UCS results for the consecutive amount of POFA geopolymer addition are 15.10 kPa, 30.05 kPa, 37.90 kPa, and 9.71 kPa. In conclusion, using POFA-based geopolymer shows potential as an effective and sustainable solution for improving the strength characteristics of peat soils with a notable maximum amount of addition at 15%. This stabilization technique could provide a viable method for infrastructure development in peatland areas.